2015
DOI: 10.1002/app.42811
|View full text |Cite
|
Sign up to set email alerts
|

Physicomechanical properties of wollastonite (CaSiO3)/styrene butadiene rubber (SBR) nanocomposites

Abstract: The purpose of this study was to investigate the effect of bare wollastonite (BW) and modified wollastonite (MW) nano‐rods into the styrene butadiene rubber (SBR). SBR nanocomposites were prepared by the incorporation of different wt % (0.3–4.5) of BW and MW nanorods. All nanocomposites were characterized by thermal gravimetric analyzer (TGA) and differential scanning calorimeter (DSC). The particle size and morphology of BW and MW nanorods were characterized by field‐emission scanning electron microscope (FE‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…The characteristic bands at 2915 and 2854 cm −1 are assigned to C-H stretching deformation of -CH 3 and -CH 2 - in SBR structure unit3435. Moreover, with the increasing of DCP content, the intensity of the peaks from sample 1 to 6 is increased, which is related to the decomposition of DCP.…”
Section: Resultsmentioning
confidence: 92%
“…The characteristic bands at 2915 and 2854 cm −1 are assigned to C-H stretching deformation of -CH 3 and -CH 2 - in SBR structure unit3435. Moreover, with the increasing of DCP content, the intensity of the peaks from sample 1 to 6 is increased, which is related to the decomposition of DCP.…”
Section: Resultsmentioning
confidence: 92%
“…The wollastonite nano-rods (WNRs), with an average diameter of 150-200 nm and length of 1-1.5 m, were synthesized by the hydrothermal microemulsion technique (Chatterjee et al, 2015). The nanorods were subsequently modified by the silane coupling agent, triethoxyvinylsilane (TEVS).…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…The hydrothermal microemulsion technique (Chatterjee, Khobragade, & Mishra, 2015) has been used to synthesize one-dimensional (1D) CaSiO 3 nanorods, which were then encapsulated by PS using cetyl trimethyl ammonium bromide (CTAB) and sodium dodecyl sulphate (SDS) as surfactants via an atomized microemulsion technique. To the best of our knowledge, limited studies have been reported on the encapsulation of CaSiO 3 nanorods using a microemulsion-assisted route, which consumes less reaction time with a high percentage of grafting.…”
Section: Introductionmentioning
confidence: 99%
“…SBR nanocomposites based on Octadecyl amine (O‐Hc) modified nanoclay show improved mechanical properties, as compared to SBR. The effect of bare wollastonite (BW) and modified wollastonite (MW) nanorods on the physicomechanical properties of SBR was investigated . SBR nanocomposites were prepared by the incorporation of different wt% (0.3–4.5) of BW and MW nanorods.…”
Section: Introductionmentioning
confidence: 99%